Andean Archaeology II
XIV, 376 p.
Keywords: The origins and development of civilization are vital components to the understanding of the cultural processes that create human societies. Comparing and contrasting the evolutionary sequences from different civilizations is one approach to discovering their unique development. One area for comparison is in the Central Andes where several societies remained in isolation without a written language. As a direct result, the only resource to understand these societies is their material artifacts. In this second volume, the focus is on the art and landscape remains and what they uncover about societies of the Central Andes region. The ancient art and landscape, revealing the range and richness of the societies of the area significantly shaped the development of Andean archaeology. This work includes discussions on: - pottery and textiles; - iconography and symbols; - ideology; - geoglyphs and rock art. This volume will be of interest to Andean archaeologists, cultural and historical anthropologists, material archaeologists and Latin American historians.